Transdisciplinary Management in Welcoming the Industrial Revolution 4.0 - Putra Mahendra Gunawan Nasution; Fakhruddin Azmi; Nurika Khalila Daulay (Institute of Computer Science (IOCS), 2022)
This study aims to determine the importance of a transdisciplinary management approach in solving various problems that exist in facing the industrial revolution 4.0 which has an impact in all fields such as education, economics, politics, and industry. This research uses a literature research method with a qualitative descriptive approach that examines data sources consisting of literature and various scientific journals related to the research theme. The results of the study explained that in solving problems faced in the industrial era 4.0, a transdisciplinary management approach is needed that integrates and combines various disciplines that give birth to new perspectives from various views together to produce comprehensive solutions and problem-solving.